Diabetic retinopathy in native and non-native Sarawakians -Findings from the Diabetic eye registry - PS, Mallika; Cheah, W.L (Malaysian Medical Association, 2012)
This study aims to determine the risk factors associated with diabetic retinopathy (DR) among natives and nonnatives Sarawakians who were seen at 3 public hospitals and one health clinic in Sarawak. It is a cross sectional study where data on patients with DM were collected by staff at these healthcare facilities and entered into the web-based Diabetic Eye Registry. Univariate and multivariate analysis was used to determine the association factors for DR. DR was significantly less associated with natives (24.4%) compared to non-native Sarawakians (34.1%) (p <0.001). The odds of getting DR was higher in patients whose duration of DM was more than 20 years (OR=2.6), who have renal impairment (OR= 1.7) and non-natives (OR =1.4).